2022
DOI: 10.1101/2022.11.21.517310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetraspanner-based nanodomains modulate BAR domain-induced membrane curvature

Abstract: Topography is a critical feature driving formation and dynamics of protein and lipid domains within biological membranes. The yeast plasma membrane (PM) has provided a powerful model system to study lateral domain formation, including characteristic BAR domain-induced PM furrows. Currently, it is not clear how the components involved in the establishment of these furrows cooperate to precisely regulate local PM topography. Here we report opposing functions for the Sur7 and Nce102 families of tetraspanner prote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Presumably, once the eisosomes are freed from the plasma membrane by our gentle purification methods, the Pil1/Lsp1 lattice realigns to form a helical conformation around a lower-energy tubular state of the plasma membrane lipids to which it is bound. Alternatively, the eisosomes that we have isolated were already in a tubulated state in vivo, a behavior that has been observed in deletion strains of the eisosome-resident Sur7-family proteins , in palmitoylcarnitine-treated S. cerevisiae 41 , and upon Pil1 overexpression in S. pombe 42,43 .…”
Section: Isolation Of Native-like Eisosome Filamentsmentioning
confidence: 69%
“…Presumably, once the eisosomes are freed from the plasma membrane by our gentle purification methods, the Pil1/Lsp1 lattice realigns to form a helical conformation around a lower-energy tubular state of the plasma membrane lipids to which it is bound. Alternatively, the eisosomes that we have isolated were already in a tubulated state in vivo, a behavior that has been observed in deletion strains of the eisosome-resident Sur7-family proteins , in palmitoylcarnitine-treated S. cerevisiae 41 , and upon Pil1 overexpression in S. pombe 42,43 .…”
Section: Isolation Of Native-like Eisosome Filamentsmentioning
confidence: 69%
“…An important remaining question is why FLPs are localized in MCCs. Although the exact lipidic composition of MCCs is still lacking, evidence suggests that MCCs are enriched in sterols and phospholipids, including unsaturated phospholipids, 13,15,19,62 and depleted in the saturated-fatty-acid-containing sphingolipids. 14,67,68 Such a lipidic composition would make MCCs more sensitive to peroxidation than the rest of the plasma membrane, thus requiring increased levels of active, ubiquinol-producing FLPs.…”
Section: Open Accessmentioning
confidence: 99%
“…10,18 In the absence of Pil1 or Nce102, MCC/ eisosome plasma membrane patches disassemble, and eisosome-resident proteins either become homogeneous at the plasma membrane or relocalize to the cytoplasm. 10,12,18 MCCresident membrane proteins include tetraspan members of the Nce102/MARVEL and Sur7 families and several nutrient transporters 9,19 (Figure 1A). Eisosomes host regulators of sphingolipid biosynthesis and membrane stress, participating in the spatial separation of components of signaling cascades, including TORC2.…”
Section: Introductionmentioning
confidence: 99%
“…Many proteins localise to eisosomes, such as core structural proteins, post-translational modifiers, tetraspan membrane proteins and uncharacterised factors ( Foderaro et al, 2017 ). For example, the tetraspanner Nce102, which functions as a sphingolipid sensor and promotes membrane curvature ( Fröhlich et al, 2009 ; Haase et al, 2022 preprint; Vaskovicova et al, 2020 ; Zahumenský et al, 2022 ), and Seg1, a stability factor that operates upstream of eisosome formation ( Moreira et al, 2012 ; Seger et al, 2011 ). A screen for phosphatidylinositol (4,5)-bisphosphate [PI(4,5)P 2 ] regulators has revealed that the eisosome factors Slm1 and Slm2 bind lipids, are required for proper eisosomal organisation, and integrate with TORC2 signalling and lipid synthesis ( Audhya et al, 2004 ; Berchtold et al, 2012 ; Fadri et al, 2005 ; Kamble et al, 2011 ; Nagaya et al, 2002 ; Riggi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%